Clinical, electrophysiological, and imaging study in essential tremor-Parkinson's disease syndrome. (November 2018) - Arabia, Gennarina; Lupo, Angela; Manfredini, Lucia Ilaria; Vescio, Basilio; Nisticò, Rita; Barbagallo, Gaetano; Salsone, Maria; Morelli, Maurizio; Novellino, Fabiana; Nicoletti, Giuseppe; Quattrone, Andrea; Cascini, Giuseppe Lucio; et al.
Abstract: Introduction: Essential tremor-Parkinson's disease (ET-PD) syndrome is a clinical condition in which individuals with a long-lasting history of Essential tremor (ET) eventually develop Parkinson's disease (PD). The aim of the study was to investigate the accuracy performances of clinical, neurophysiological, and imaging biomarkers in differentiating patients affected by ET-PD syndrome from patients with ET or PD. Methods: Nineteen patients affected by ET-PD syndrome, 48 ET patients, and 37 tremor-dominant PD (t-PD) patients were included. Electrophysiological studies, including blink-reflex recovery cycle and tremor parameters analyses, were performed in all groups. Nigro-striatal and cardiac sympathetic denervation were also investigated. Sensitivity, specificity and accuracy of clinical, electrophysiological, and radiological features in differentiating ET-PD syndrome from ET and PD were calculated. Results: ET-PD patients had significantly lower rigidity (p = 0.007) and higher postural/kinetic tremor (p = 0.007) scores, in comparison to t-PD patients. ET-PD patients, differently from PD patients, had a synchronous pattern of resting tremor and, differently from ET patients, had abnormal blink-reflex recovery cycle. ET-PD patients also showed reduced nigro-striatal and cardiac sympathetic uptakes, albeit to a lesser extent than in PD patients. The highest accuracy values were found for the synchronous pattern of resting tremor (97.1%) in distinguishing ET-PD from PD, and for presence of abnormal blink-recovery cycle (100%) in distinguishing ET-PD syndrome from ET. Conclusion: Our study demonstrates that some electrophysiological parameters, such as a synchronous resting tremor pattern and the abnormal blink-recovery cycle were the most accurate biomarkers in distinguishing patient with ET-PD syndrome from those with ET or those with PD. Highlights: ET-PD is a syndrome in which individuals with a long history of ET eventually develop PD. Clinical and instrumental data were compared among ET-PD, ET, and t-PD patients. ET-PD had lower rigidity and higher tremor scores than t-PD with similar disease duration. Tremor pattern and BRrc accurately distinguished ET-PD from PD and ET, respectively.